2015
DOI: 10.1002/jee.20079
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Constraining of Student Design Practices

Abstract: BackgroundEngineering design is of significant interest to engineering educators. As yet, how the higher education context shapes student outcomes in engineering design courses remains underexplored. Since design courses are the primary way students are taught the critical topic of design, it is important to understand how the institutional and organizational contexts shape student outcomes and how we could improve design projects, given the context.PurposeWe sought to answer two questions: What aspects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Our most important methodological implications concern how to evaluate group development interventions in engineering education, including not only group norm exercises, but also, for instance, group formation practices and exercises focused on evaluating group member performance. While previous research has observed groupwork up-close and over time (Goncher & Johri, 2015;Kaygan, 2023), most research on group development interventions-perhaps unsurprisingly-follow an intervention research logic, evaluating activities and support structures mainly through quantitative pre-and post-measures of group dynamics and group performance (Aaron et al, 2014;Murzi et al, 2020;Pertegal-Felices et al, 2019). We believe this to be an important research approach, especially when isolating design elements and properly controlling for confounding variables.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our most important methodological implications concern how to evaluate group development interventions in engineering education, including not only group norm exercises, but also, for instance, group formation practices and exercises focused on evaluating group member performance. While previous research has observed groupwork up-close and over time (Goncher & Johri, 2015;Kaygan, 2023), most research on group development interventions-perhaps unsurprisingly-follow an intervention research logic, evaluating activities and support structures mainly through quantitative pre-and post-measures of group dynamics and group performance (Aaron et al, 2014;Murzi et al, 2020;Pertegal-Felices et al, 2019). We believe this to be an important research approach, especially when isolating design elements and properly controlling for confounding variables.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 97%
“…Group development can be viewed both as (i) a project that students and teachers sometimes engage in to improve group functioning, and (ii) a process of change and, potentially, improvement in group functioning over time, not necessarily being the product of purposeful effort. Literature on group development suggests that group norms is partly a product of inputs to group processes, including, for instance, individual group member characteristics and group composition (Parker et al, 2019;Pieterse & Thompson, 2010;Sahin, 2011), as well as social context, including, for instance, institutional practices and broader cultural values (Goncher & Johri, 2015;Tonso, 1996Tonso, , 2006. However, because students are not passive or disinterested when it comes to what is expected of group members, group norms do not develop deterministically from these inputs (Quan et al, 2015).…”
Section: The Importance Of Norm Negotiations In Developing Group Normsmentioning
confidence: 99%